ChemInform Abstract: A Keggin‐Type Structure Expanded by an Eight‐Membered Ring of Alternating Edge‐Sharing VO5 and VO6 Polyhedra: Solvothermal Synthesis, Crystal Structure, and Magnetic Properties. Issue 38 (3rd September 2015) - Rasmussen, Maren; Naether, Christian; van Leusen, Jan; Koegerler, Paul; Bensch, Wolfgang
Abstract (trenH)2(trenH2)2 [W4V13O44]·≈11H2O (tren: tris(2‐aminoethyl)‐amine) is prepared under solvothermal conditions by reacting NH4VO3 and WO3 (molar ratio of 1:1.6) in a solution of tren in H2O at pH ≈12 (sealed glass tubes, 130 °C, 3 d, 65% yield based on WO3).